Pengaruh Intensitas Penyinaran dan Frekuensi Penyiraman terhadap Pertumbuhan Bibit Kelapa Sawit di Pre Nursery - Wandani, Beno; Rusmarini, Umi Kusumastuti; Yuniasih, Betti (AGROISTA : Jurnal Agroteknologi, 2025)
Oil palm nursery is generally conducted through a two-stage system, namely the pre-nursery stage and the main nursery stage. In the pre-nursery stage, seedlings require watering of 0.1–0.3 liters per day with a watering frequency of twice daily, in the morning and evening. Meanwhile, shading serves to protect against high sunlight intensity. This study aims to investigate the effect of light intensity and watering frequency on the growth of oil palm seedlings in the pre-nursery stage. The study was conducted from June 2024 to September 2024. It employed a factorial experiment method arranged in a split-plot design with two factors. The first factor (main plot) was light intensity, consisting of three levels: 3,500, 2,000, and 1,000 foot candles. The second factor (subplot) was watering frequency, consisting of three levels: twice a day, once a day, and once every two days with a water volume of 200 ml/day. Each treatment was replicated four times. Data were analyzed using analysis of variance (ANOVA), and if significant differences were found, the Duncan Multiple Range Test (DMRT) was applied. The ANOVA results showed a significant interaction between light intensity and watering frequency on the growth of oil palm seedlings in the pre-nursery stage, specifically in the parameter of seedling fresh weight. Light intensities of 1,000 and 2,000 foot candles resulted in taller seedlings compared to 3,500 foot candles, while a light intensity of 3,500 foot candles influenced root growth. Watering frequencies of twice a day and once a day showed better seedling growth compared to watering once every two days.